Rancang Bangun Sistem Informasi Manajeman Kepegawaian (Studi Kasus Pada PMI Kabupaten Kudus) - Nugraha, Fajar; Aditya, Dian; Fithri, Diana Laily; Latifah, Noor (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Management Information System (MIS) is an information system that is specifically used by organizations for managing all matters relating to the management function and can be used in assisting organizational decision making. In its implementation, the Management Information System can function optimally if it is supported by quality technology and resources and has a commitment to organizational development. The management of the personnel management system at PMI Kudus Regency currently has several obstacles in processing its personnel data which results in problems due to errors in which data processing is still done conventionally, employee data synchronization cannot be done properly because data recording has not been carried out in an integrated manner. Based on some of these constraints, the research developed a web-based personnel management information system design using the UML design method. It is hoped that by utilizing this personnel management system the management of personnel data at PMI Kudus Regency can be managed properly and effectively in order to improve services, especially in the field of personnel. Keywords: information systems, management, personnel.